(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2020)
Two weeks into my new role as a Young Carer Development Worker, I did not picture myself typing away at my home computer in my dressing gown and hiking socks. I expected to be ‘hitting the ground running’ and really getting to grips with the dynamic, face-to-face work that Edinburgh Young Carers (EYC) delivers. Like many others in our field, I feel at a bit of a loss and helpless trying to fulfil the role that I love during this period of social isolation. This time of fear, uncertainty and frustration has brought huge challenges for services, workers and communities. Perhaps most starkly for those individuals and families who are already struggling. As a new member of the team, I am in no way an authority on the issues that affect young carers. However, luckily for myself (and you the reader!), I am working with a team full of experts who have been kind enough to highlight the issues impacting on EYC’s children and young people in these, to use the stock phrase of 2020, ‘unprecedented times’.